2022
DOI: 10.3389/fpsyg.2022.856430
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Teacher–Student Rapport and Teacher Support as Predictors of Chinese EFL Students’ Affective Learning

Abstract: Students’ affective learning is critical for their academic success; therefore, considerable attention has been devoted to the role of various student-related and teacher-related factors as predictors of student affective learning. Notwithstanding, the impact of two important teacher-related factors, namely teacher–student rapport and teacher support, has not been adequately researched. To address this gap, the present study sought to explore the role of teacher support and teacher–student rapport in Chinese E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Hsieh [11] reported that online resources enhance student interaction, which in turn helps to accomplish online collaborative English writing tasks. Sun and Shi [38] pointed out that friendly teacher-student relationships benefit online foreign language learning, and that teachers' guidance and assistance support students' accomplishment of language learning tasks. Moreover, Rienties et al [12] indicated the importance of appropriate course design in online foreign language learning.…”
Section: Online Learning Environmentmentioning
confidence: 99%
“…Hsieh [11] reported that online resources enhance student interaction, which in turn helps to accomplish online collaborative English writing tasks. Sun and Shi [38] pointed out that friendly teacher-student relationships benefit online foreign language learning, and that teachers' guidance and assistance support students' accomplishment of language learning tasks. Moreover, Rienties et al [12] indicated the importance of appropriate course design in online foreign language learning.…”
Section: Online Learning Environmentmentioning
confidence: 99%
“…So, teacher’s facial expression could affect students’ learning attitude, motivation, and the qualities of interaction between teacher and students. Chinese EFL students’ affective learning is largely influenced by teacher-student rapport and teacher support ( Sun and Shi, 2022 ). Higher-level actions as one of mediated actions proposed by Norris, could support MDA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…in students’ learning achievement [e.g., Refs. [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ], among others]. Teacher personal traits, also called personal resources, refer to the physical and emotional resources teachers bring with them to educational environments [ 12 ].…”
Section: Introductionmentioning
confidence: 99%